ECOLOGICAL IMPERATIVE OF LOGISTIC DEVELOPMENT - K. Matevosova (Вестник университета)
The problems of the ekologo-focused logistic development of economy are considered in the article. The arguments proving necessary of creation of the ecological restrictions for economic activity capable to consider interests of the environment and future generations are presented. Possibilities of modification of a conceptual framework, structure of logistic systems taking into account an ecological imperative are shown. The modern concept of the closed logistic system taking into account interests of all economic entities and the environment is submitted. Tasks which need to be solved for implementation of the ekologo-focused logistic management of economy are formulated.